2010
DOI: 10.3109/17453671003667150
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk is not increased after conventional hip arthroplasty

Abstract: Background and purposeWear debris from conventional total hip arthroplasty (THA) induces chromosomal aberrations and DNA damage, which may promote cancerogenesis. A long latent period is required for solid tumors. We therefore re-analyzed a large THA cohort for cancer.Patients and methodsWe updated a cohort of 24,636 patients with primary osteoarthritis and metal-on-polyethylene THA who had been entered in the Finnish Arthroplasty Register between 1980 and 1995, and linked it to the Finnish Cancer Registry for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
55
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 41 publications
10
55
0
Order By: Relevance
“…Systemic exposure to chromium, cobalt, nickel, and aluminium alloys can occur because of the formation of metal wear nanoparticles that are released both from metal-on-metal and metal-on-polyethylene bearings, resulting in a postoperative increase in metal ion levels at different organ sites, especially those comprising the lymphoreticular system. These particles circulate locally and systemically, penetrate cell plasma membranes, bind to cellular proteins and enzymes, cause chromosome aberrations and DNA damage, modulate cytokine expression, and might, therefore, cause long-term increased risks of cancer (Visuri et al , 2010; Mäkelä et al , 2012; Polyzois et al , 2012). Although a Working Group established by the International Agency for Research on Cancer concluded that there is inadequate evidence in humans for the carcinogenicity of metallic implants, metallic foreign bodies, and orthopaedic implants of complex composition (IARC Monographs on the Evaluation of Carcinogenic Risks to Humans, 1999), this finding does not rule out a risk of cancer entirely, and the evidence reviewed pre-dated the emergence of the modern generation of metal-on-metal hip prostheses (Cohen, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic exposure to chromium, cobalt, nickel, and aluminium alloys can occur because of the formation of metal wear nanoparticles that are released both from metal-on-metal and metal-on-polyethylene bearings, resulting in a postoperative increase in metal ion levels at different organ sites, especially those comprising the lymphoreticular system. These particles circulate locally and systemically, penetrate cell plasma membranes, bind to cellular proteins and enzymes, cause chromosome aberrations and DNA damage, modulate cytokine expression, and might, therefore, cause long-term increased risks of cancer (Visuri et al , 2010; Mäkelä et al , 2012; Polyzois et al , 2012). Although a Working Group established by the International Agency for Research on Cancer concluded that there is inadequate evidence in humans for the carcinogenicity of metallic implants, metallic foreign bodies, and orthopaedic implants of complex composition (IARC Monographs on the Evaluation of Carcinogenic Risks to Humans, 1999), this finding does not rule out a risk of cancer entirely, and the evidence reviewed pre-dated the emergence of the modern generation of metal-on-metal hip prostheses (Cohen, 2011).…”
mentioning
confidence: 99%
“…Two early cohort studies of cancer risk following THA found an increased risk of lymphohaematopoietic malignancies (Gillespie et al , 1988; Visuri and Koskenvuo, 1991), but apart from an excess of multiple myeloma emerging during long-term follow-up (Signorello et al , 2001), other studies (Mathiesen et al , 1995; Nyrén et al , 1995; Gillespie et al , 1996; Visuri et al , 1996, 2010; Olsen et al , 1999; Paavolainen et al , 1999; Goldacre et al , 2005; Mäkelä et al , 2012) have not shown an excess risk of these cancers. However, some other studies have reported excess risks of melanoma of the skin (Nyrén et al , 1995; Olsen et al , 1999; Signorello et al , 2001; Mäkelä et al , 2012), prostate cancer (Nyrén et al , 1995; Signorello et al , 2001), kidney cancer (Nyrén et al , 1995), and basal cell carcinoma of the skin, specifically in patients with modern generation metal-on-metal hip replacements (Mäkelä et al , 2012).…”
mentioning
confidence: 99%
“…[14] Although both ions are known to be genotoxic,[41] so far epidemiological studies have failed to show an increase in cancer related mortality after hip arthroplasty [32]. [42][43] …”
mentioning
confidence: 99%
“…7 Several long term register studies and meta-analyses of patients with metal-on-polyethylene and older metal-on-metal hip articulations (1950s and 1960s) suggest no increase in overall cancer risk for patients with joint replacement (some studies also included patients who had undergone knee replacement surgery). [8][9][10][11] Increased risk for melanoma and possibly urinary tract and prostate cancers were, however, reported in some studies. The question of whether the increased risk is associated with the underlying disease (osteoarthritis) or the treatment (joint replacement) remains unclear.…”
mentioning
confidence: 98%